AGILE GOVERNANCE DALAM PELAYANAN PUBLIK DI PERUSAHAAN UMUM DAERAH GIRI TIRTA KABUPATEN GRESIK - Shava Berlinda Putri; M.Husni Tamrin; Sri Wahyuni; Budi Rianto (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2022)
The Regional Public Company (Perumda) Giri Tirta as the largest water provider in Gresik Regency is certainly not immune from various kinds of problems every day, such as jammed water, broken meters, cloudy water, leaky pipes. In overcoming the problems faced, the Regional Public Company (Perumda) Giri Tirta, Gresik Regency launched an online-based complaint application known as Gita Ceria Mobile. This is intended so that customers of the Giri Tirta Regional Public Company (Perumda) can more easily communicate with parties from the Giri Tirta Regional Public Company (Perumda) regarding the services provided. The purpose of this study is to describe and analyze Agile Governance in Public Services at the Giri Tirta Regional Public Company (Perumda), Gresik Regency. This study uses the concept of Agile Governance where this theory is the ability of organizations to respond quickly to unexpected changes in meeting the demands and needs of an increasingly changing society. Agile is here to improve organizational capabilities in utilizing information and communication technology. The method used by researchers is using descriptive qualitative. Informants in this study were employees of the Giri Tirta Regional Public Company (Perumda) Gresik Regency and customers of the Giri Tirta Regional Public Company Perumda. Data collection techniques using interviews, observation and documentation. The existing findings show that the Giri Tirta Regional Public Company (Perumda) Gresik Regency has strengthened cooperation with the private sector which has succeeded in increasing water distribution. The findings in the field show that customers are very involved in the innovations provided by the Regional Public Company (Perumda) but the lack of socialization means that not all customers know about it. In terms of speed, accuracy, and success the Regional Public Company (Perumda) is effective in carrying out the program but there are problems in the queue following up on customer reports. In meeting customer needs, employees of the Regional Public Company (Perumda) have conducted useful training to expand capabilities and create new innovations.